Saree Cancer in Indian Woman Treated Successfully with Multimodality Management : A Case Report - Takalkar, Unmesh Vidyadhar; Asegaonkar, Shilpa Balaji; Kodlikeri , Pushpa; Kulkarni, Ujwala; Borundiya , Virendrakumar; Advani, Suresh H. (Perspective of Recent Advances in Medical Research Vol. 5, 2023)
The present case of saree cancer at waistline, which was successfully managed with multimodality therapy consisting of surgery, chemotherapy and radiotherapy. Indian women frequently wear sarees, a traditional garment with one end draped over the shoulder and a thick cord tightened around the waist. Tight knot in the same place, sweat, soiling and continuous use can cause pigmentation, scaling of the waist and even transform to malignancy. Here, we describe a case of saree cancer that was successfully treated with multiple modalities. A 50-year-old woman was referred to our hospital (India) for itching and non-healing ulcerative lesion on waistline. She was wearing saree continuously for 34 years with knot at the same place.Imaging with magnetic resonance suggested lymph node metastasis and ulcerative growth. Hertopathological analysis confirmed it was a squamous cell carcinoma after she had wide local excision. Consequently, she received concurrent chemotherapy and radiation treatment. . She is now (2 years after the completion of treatment) in remission state. Awareness of saree cancer among Indian is important to avoid malignant lesions at waistline. Multimodality management with surgery, chemotherapy and radiotherapy is ideal mean for good outcome.